Study the Effect of Methotrexate and Etanercept Therapies on the Serum Levels of Galectin-3 and Matrix metalloproteinase-3 in Iraqi Patients with Rheumatoid Arthritis - Hameed, Muna. R.; Khaleel, Fayhaa. M.; Gorial, Faiq I. (Iraqi Journal of Science, 2026)
Rheumatoid arthritis (RA) is a chronic autoimmune inflammatory disorder characterized by inflammatory joint damage, leading to stiffness, swelling, and pain. The biomarkers galectin-3 (Gal-3) and matrix metalloproteinase-3 (MMP-3) have been implicated in RA pathogenesis. This study aimed to observe the effect of Methotrexate (MTX) and Etanercept (ETA) medications on serum Gal-3 and MMP-3 levels of Iraqi RA patients. Gal-3 and MMP-3 were measured in sera of 92 RA patients and 38 control using ELISA assay. Patients were categorized into groups according to received treatment: MTX, ETA, combined MTX plus ETA, and untreated patients (Un-T). The clinical disease activity index (CDAI) was calculated for patients. The Gal-3 levels for MTX reduced significantly to control (P=0.031) and ETA (P=0.002). MMP-3 level elevated in ETA than control (P=0.005), and decreased in MTX than ETA (P=0.008). MTX monotherapy decreases the Gal-3 and MMP-3 levels without attaining the desired mild activity. ETA monotherapy reduces Gal-3 levels to within the normal range and achieves mild disease activity, but it does not significantly affect MMP-3 levels. Both biomarkers are useful for monitoring the effectiveness of MTX treatment more accurately than simply observing disease activity. Gal-3 and MMP-3 association was slightly affected in treatment groups but still statistically significant.